News Media Effects on Policy Priorities: A Second-Level Agenda-Setting Analysis of Belt and Road Initiative (BRI) Projects in Myanmar - Zeyar Oo; Yonghong Dai (Journalism and Media)
This study investigates the impact of the media’s secondary agenda-setting on public perception and policy priorities regarding the Belt and Road Initiative (BRI) projects in Myanmar from to 2011–2024. Three hypotheses (Hs) were examined: H1 posits that media coverage aligns with public and policy perspectives; H2 proposes that media emphasis on specific attributes influences their prominence in public opinion and policymaking; and H3 suggests that public opinion mediates the relationship between media coverage and policy priorities, indicating an indirect media influence on policymaking. This study employed a cross-sectional research design, utilizing both quantitative content analysis and survey methodologies. The content comprises the analysis of two news outlets’ coverage (n = 144), surveys with 385 respondents (n = 385), and in-depth interviews with 30 participants (n = 30), and the findings revealed a significant positive correlation between media coverage and public opinion and policy priorities (r = 0.86, r = 0.81, respectively). SEM path analysis reveals that the media agenda indirectly shapes the policy agenda through the public agenda, with an indirect effect path coefficient of 0.718, highlighting the media’s role in policymaking processes. This is evidenced by a significant correlation between media coverage and public opinion (p < 0.05), and a strong direct association between public opinion and policy priorities (p < 0.05). This study extends the agenda-setting theory by empirically demonstrating the media’s indirect effect on policy formation in global infrastructure projects within a developing Southeast Asian country. Future studies should examine the evolution of media patterns across different administrations, including the current one. The results also suggest examining the broader media portrayal of governance issues and conducting extensive research on the media’s impact on public opinion.